Cross-cultural adaption and psychometric investigation of the German version of the Evidence Based Practice Attitude Scale (EBPAS-36D) - Katharina Szota; Jonathan F. B. Thielemann; Hanna Christiansen; Marte Rye; Gregory A. Aarons; Antonia Barke (BMC, 2021)
Abstract Background The implementation of evidence-based practice (EBP) in mental health care confers many benefits to patients, and research into factors facilitating the implementation of EBP is needed. As an important factor affecting the implementation of EBP, service providers' attitudes toward EBP emerged. The Evidence-Based Practice Attitude Scale (EBPAS-36) is an instrument with good psychometric characteristics that measures positive and ambivalent attitudes toward EBP. However, a German version is missing. The present study therefore aims to provide a validated German translation of the EBPAS-36. Methods The scale was translated and back-translated as recommended by standard procedures. German psychotherapists were recruited to participate in an online survey. They provided demographic and professional information, completed the EBPAS-36, the Implementation Climate Scale (ICS) and the Intention Scale for Providers (ISP). Standard item and reliability analyses were conducted. Construct validity was evaluated with exploratory (EFA) and confirmatory factor analyses (CFA) in two subsamples (random split). Convergent validity was tested by predicting a high positive correlation of the EBPAS-36D with two scores of attitudes of the ISP and an interest in EBP score. It was tested whether the EBPAS-36D predicts the intention to use EBP. Results N = 599 psychotherapists participated in the study. The item analyses showed a mean item difficulty of p i = 0.64, a mean inter-item correlation of r = 0.18, and a mean item-total correlation of r itc = 0.40. The internal consistency was very good for the total scale (α = 0.89) and ranged from adequate to very good for the subscales (0.65-0.89), indicating high reliability. The original factor structure showed an acceptable model fit (RMSEA = 0.064 (90% CI = 0.059-0.068); SRMR = 0.0922; AIC = 1400.77), confirming the 12-factor structure of the EBPAS-36. However, a second-order factor structure derived by the EFA had an even better model fit (RMSEA = 0.057 (90% CI = 0.052-0.062); SRMR = 0.0822; AIC = 1274.56). When the EBPAS-36D was entered in a hierarchical regression model with the criterion Intention to use EBP, the EBPAS-36D contributed significantly to the prediction (Change in R 2 = 0.28, p < 0.001) over and above gender, age and participants' report of ever having worked in a university context. Conclusions The present study confirms good psychometric properties and validity of a German version of the EBPAS-36 in a sample of psychotherapists.